MicroRNA-374b induces endothelial-to-mesenchymal transition and early lesion formation through the inhibition of MAPK7 signaling - Vanchin, Byambasuren; Offringa, Emma; Friedrich, Julian; Brinker, Marja GL; Kiers, Bianca; Pereira, Alexandre C.; Harmsen, Martin C.; Moonen, Jan-Renier AJ; Krenning, Guido (The journal of pathology, 2019)
Endothelial-mesenchymal transition occurs during intimal hyperplasia and neointima formation via mechanisms that are incompletely understood. Endothelial MAPK7 signaling is a key mechanosensitive factor that protects against endothelial-mesenchymal transition, but its signaling activity is lost in vessel areas that are undergoing pathological remodeling. At sites of vascular remodeling in mice and pigs, endothelial MAPK7 signaling was lost. The TGFβ-induced microRNA-374b targets MAPK7 and its downstream effectors in endothelial cells, and its expression induces endothelial-mesenchymal transition. Gain-of-function experiments, where endothelial MAPK7 signaling was restored, precluded endothelial-mesenchymal transition. In human coronary artery disease, disease severity is associated with decreased MAPK7 expression levels and increased miR-374b expression levels. Endothelial-mesenchymal transition occurs in intimal hyperplasia and early lesion formation and is governed in part by microRNA-374b-induced silencing of MAPK7 signaling. Restoration of MAPK7 signaling abrogated these pathological effects in endothelial cells expressing miR-374b. Thus, our data suggest that the TGFβ-miR-374b-MAPK7 axis plays a key role in the induction of endothelial-mesenchymal transition during intimal hyperplasia and early lesion formation and might pose an interesting target for antiatherosclerosis therapy. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.
First published: 22 November 2018
Gesehen am 24.03.2020